Hermeneutics, Social Criticism and Everyday Education Practice - Włodarczyk, Rafał. Red. (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The individual chapters written by scholars of the Department of General Pedagogy at the University of Wrocław included in the volume offered to the Readers, showcase selected variants and problems of the hermeneutical and critical approaches to educational practice and research. The general pedagogy we practice in this way reveals its interdisciplinary character, drawing on the resources and achievements of philosophy, sociology, psychology, cultural anthropology, religious studies, and political sciences.
Keywords: hermeneutics; social criticism; education practice; utopia